The concept yrys “happiness” in the linguistic worldview of the Altaians - Tybykova Лариса (Turkic Studies Journal, 2022)
The concept «yrys» in the linguistic worldview of the Altaians, as one of the Turkic peoples, is one of the defining characteristics of the spiritual and emotional essence of man. In the Altaic linguistic worldview, the concept «yrys», despite its ideological and psychological significance, has not been studied in Altaic linguistics. This article discusses the semantic and functional properties of the lexical units of the Altai language, which verbalize the idea of happiness among its speakers. The specific objectives of the study also include the analysis of linguacultural specifics and the semantic structure of the concept of happiness in the linguistic worldview of the Altaians. The concept yrys «happiness» is objectified in the Altai language by ready-made lexemes, phrase combinations from the lexico-phraseological system of the language; proverbs and sayings, structural and positional schemes of sentences that carry typical propositions (syntactic concepts); texts and collections of texts (if necessary, explication or discussion of the content of complex, abstract or individually – author’s concepts). Analysis of these values, as well as the values of this word presented in the dictionaries and in the surveys of informants, provides a reason to conclude that in the mentality of the Altaians, happiness is understood as luck and as a happy proportion when various life circumstances are successfully folded. The concept of «yrys» happiness is associated with the deep internal satisfaction of man with his life. The study of respondents makes it possible to conclude that modern Altaians have a clear idea of happiness and that education affects the hierarchy of the components of happiness. For the younger generation, love, mutual understanding and success are more important than Altaians of the older generation for health, prosperity and well-being.